2004
DOI: 10.1111/j.0041-1132.2004.04166.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of peripheral blood progenitor cell harvest based on peripheral blood hematopoietic progenitor cell counts enumerated by the Sysmex SE9000

Abstract: This might be the first prospective study showing the PB HPC level for timing PBPC harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…However, it is questionable whether the appropriate timing of PBSCH can be judged with a single cut-off level for the HPC count. In previous studies, the optimal cut-off level of the HPC count varied from 5 to 50/ µL [5,8,12,13]. Jo et al reported that a rate of HPC increase of more than 2.0/µL/day is a good indicator [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is questionable whether the appropriate timing of PBSCH can be judged with a single cut-off level for the HPC count. In previous studies, the optimal cut-off level of the HPC count varied from 5 to 50/ µL [5,8,12,13]. Jo et al reported that a rate of HPC increase of more than 2.0/µL/day is a good indicator [10].…”
Section: Discussionmentioning
confidence: 99%
“…9 In mobilization with chemotherapy plus G-CSF, suggested predictive factors for initiating harvests have included the peripheral WBC count, circulating CD34 þ cells, the peripheral absolute monocyte count and the platelet count. 10,13 The measurement of CD34 þ cells in peripheral blood before PBSC harvest has begun to be used, but it is too labor intensive to determine this value every day around the time of PBSC harvest. Furthermore, when chemotherapy is used for PBSC mobilization, myelosuppression induced by chemotherapy is inevitable, and we might repeat unwanted chemotherapy simply to mobilize PBSC, and thus cause additional costs for patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it takes longer to reach the peak of circulating CD34 þ cells following pre-mobilization chemotherapy, especially in heavily pre-treated patients. Although the daily measurement of blood CD34 þ cells from the day of rising WBC to the day of apheresis has been used to determine the time to start collection, 10 the frequent measurement of CD34 þ cells is both time consuming and labor intensive. We sometimes miss the opportunity for collection when WBC is rising very slowly.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Since July 2002, apheresis was started only if the peripheral blood (PB) HPC count exceeded 5/ml. 13 In YUMC, PBPC collection was started when PB CD34 þ cell count exceeded 10/ml. In both centers, PBPC were collected with a continuous-flow large-volume blood cell separator (Fenwal CS3000 plus, Baxter healthcare, Deerfield, IL, USA).…”
Section: MC Pbpc Harvest and Cd34 Cell Quantitationmentioning
confidence: 99%
“…There were no between-group differences in apheresis initiation criteria and days of G-CSF use. Aphereses were started on day 16 (median) in the ESHAP (range [13][14][15][16][17][18][19][20][21][22] and on day 14 (median) in the HDCY group (range 12-22) (P ¼ 0.002). The number of total MNCs collected was significantly greater in the HDCY group (P ¼ 0.002), but the number of total CD34 þ cells was significantly higher in the ESHAP group (P ¼ 0.003).…”
Section: Pbpc Harvest Yields For the Eshap And Hdcy Groupsmentioning
confidence: 99%